Powder Bed Fusion of Multimaterials - Thywill Cephas Dzogbewu; Deon de Beer (Journal of Manufacturing and Materials Processing, 2023)
Powder bed fusion (PBF) process has been used successfully to produce 3D structures using single material properties. The current industrial demand is to use the technology to produce 3D structures of multimaterial properties. An electron beam melting (EBM) process has been used to produce 3D structures of multimaterial properties. However, due to the large beam size, the EBM process lacks geometrical accuracy, requiring a large machining allowance. A laser powder bed fusion (LPBF) process could be used to produce multimaterials with geometrical precision. However, the thermal gradient within the molten pool and the thermophysical difference between the multimaterials leads to defects (weak interfacial bonds, interlayer and intralayer cracks). Other challenges such as poor powder delivery system, powder cross-contamination, and lack of appropriate data processing software for producing 3D multimaterial structures are not yet fully resolved. Nonetheless, there have been encouraging results for producing the next generational multimaterial 3D components of intricate geometrical characteristics.